Case Report: ISPD Gene Mutation Leads to Dystroglycanopathies: Genotypic Phenotype Analysis and Treatment Exploration - Yang, Haiyan; Cai, Fang; Liao, Hongmei; Gan, Siyi; Xiao, Ting; Wu, Liwen (Frontiers in Pediatrics, 2021)
ISPD gene mutation-related diseases have high clinical and genetic heterogeneity, and no studies have yet reported any effective treatments. We describe six patients with dystroglycanopathies caused by ISPD gene mutations and analyze their genotypes and phenotypes to explore possible effective treatments. Our results confirm that the phenotype of Limb-girdle muscular dystrophies can be easily misdiagnosed as Duchenne muscular dystrophy and that exon deletions of the ISPD gene are relatively common. Moreover, low-dose prednisone therapy can improve patients' exercise ability and prolong survival and may be a promising new avenue for ISPD therapy.